Characterization of taste sensitivities to amino acids and sugars by conditioned taste aversion learning in chickens - Yuta Yoshida; Shu Fujishiro; Ryota Kawai; Fuminori Kawabata (Animal, 2024)
Taste plays an essential role in regulating the feeding behaviors of animals. The present study aimed to characterize the taste sensory profiles of amino acids and sugars in chickens. To achieve this, we employed a conditioned taste aversion learning method, which is characterized by a specific pairing of gastrointestinal malaise and taste perception. Our findings revealed that chickens were able to learn to avoid L-Val, L-Lys, and L-His through conditioned taste aversion learning, and exhibited a strong aversion to L-Arg. These results suggest that chickens are primarily sensitive to basic amino acids, including L-Lys, which is a crucial limiting amino acid in feeds. Interstingly, this sensitivity to basic amino acids in chickens contrasts with humans, who are mainly sensitive to acidic amino acids as umami taste. Furthermore, despite the absence of a mammalian sweet taste receptor gene in the chicken genome, we demonstrated that chickens learned to avoid glucose, galactose, sucrose, and maltose by conditioned taste aversion learning. Taken together, the present study provides the idea that chickens possess a gustatory perception toward specific amino acids and sugars for the detection of beneficial nutrients in their feeds.